Psoriatic Foot Involvement is the Most Significant Contributor to the Inconsistency Between PASI and DLQI: A Retrospective Study from China - Yang J; Hu K; Li X; Hu J; Tan M; Zhang M; Chen J; Kuang Y (Dove Medical Press, 2023)
Jing Yang,1,2 Kun Hu,1,2 Xingyu Li,1,2 Jingjin Hu,1,2 Minjia Tan,1,2 Mi Zhang,1,2 Junchen Chen,1,2 Yehong Kuang1,2 1Department of Dermatology, Xiangya Hospital, Central South University, Changsa, Hunan, People's Republic of China; 2National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Changsa, Hunan, People's Republic of ChinaCorrespondence: Yehong Kuang; Junchen Chen, Department of Dermatology, Xiangya Hospital, Central South University, 87 Xiangya Road, Changsha, Hunan, 410000, People's Republic of China, Tel +86-13574171102, Email yh_927@126.com; 499975690@qq.comBackground: The Psoriasis Area and Severity Index (PASI) and the Dermatology Life Quality Index (DLQI) are important evaluation tools for assessing psoriasis severity and guiding treatment options. However, the scores of PASI and DLQI are often inconsistent.Objective: This study aimed to identify the factors affecting the consistency between PASI and DLQI.Methods: The retrospective study was based on 4125 patients. We collected the PASI, DLQI, demographic and clinical characteristics data.Results: DLQI has a weak correlation with PASI (r=0.37; P< 0.001). For the DLQI > 10 groups, DLQI has almost no correlation with PASI (r=0.16; P< 0.001). There are 43.60% of mild-to-moderate patients (PASI< 10) in the DLQI> 10 groups. Our adjusted model showed that foot (OR=2.109; 95% CI:1.581- 2.815) involvement led to the greatest impairment of QoL except for PASI≥ 10 (OR=5.547; 95% CI:3.477- 8.845). Furthermore, DLQI impairment was associated with female (OR=1.336; 95% CI:1.071- 1.667); the age of 20- 39 subgroup (OR=1.795; 95% CI:1.100- 2.930); psoriatic arthritis (OR=1.718; 95% CI:1.208- 2.443); higher income (OR = 1.408; 95% CI: 1.067- 1.858); family history of psoriasis (OR=1.460; 95% CI:1.131- 1.885). Moreover, the influence of exposed lesions (such as scalp; face; neck; nails; and hands) were positively associated with severely impaired QoL.Conclusion: Dermatologists should recognize the underestimated disease burden of psoriasis patients and actively identify and treat mild-to-moderate patients with high burden. In particular, the foot was a significant contributor to the burden.Keywords: psoriasis, Dermatology Life Quality Index, Psoriasis Area and Severity Index, disease severity, retrospective study, foot